2002
DOI: 10.1016/s0005-2736(02)00409-1
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic effects of local anesthetics on rotational mobility in neuronal and model membranes

Abstract: To provide a basis for studying the molecular mechanism of pharmacological action of local anesthetics, we carried out a study of the membrane actions of tetracaine, bupivacaine, lidocaine, prilocaine and procaine. Fluorescence polarization of 12-(9-anthroyloxy)stearic acid (12-AS) and 2-(9-anthroyloxy)stearic acid (2-AS) were used to examine the effects of local anesthetics on differential rotational mobility between polar region and hydrocarbon interior of synaptosomal plasma membrane vesicles (SPMV) isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 62 publications
4
50
0
3
Order By: Relevance
“…Lidocaine induces larger fluidity changes in DPPC membranes than in POPC/cholesterol membranes, suggesting that membrane fluidization depends on the lipid composition. Its membrane effects are consistent with the previous reports of local anesthetics to fluidize artificial and synaptosomal membranes [33,40]. The membrane-acting concentrations (0.1-2 mg/mL) of lidocaine are lower than or almost correspond to its clinically used concentrations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Lidocaine induces larger fluidity changes in DPPC membranes than in POPC/cholesterol membranes, suggesting that membrane fluidization depends on the lipid composition. Its membrane effects are consistent with the previous reports of local anesthetics to fluidize artificial and synaptosomal membranes [33,40]. The membrane-acting concentrations (0.1-2 mg/mL) of lidocaine are lower than or almost correspond to its clinically used concentrations.…”
Section: Discussionsupporting
confidence: 88%
“…Besides voltage-gated sodium channels of neural and cardiac cells, local anesthetics act on membrane lipids to modify the physicochemical properties like fluidity of artificial and biological membranes, thereby directly affecting the function of biomembranes and indirectly modulating the activity of ion channels through the conformational changes of transmembrane proteins [40]. Drug-induced membrane fluidization is referred to as one of pharmacological mechanisms for local anesthetics [34].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a decrease in the rotational mobility of the fluorescent probe in the headgroup region of the membrane. Earlier reports have described membrane perturbing effects of the local anesthetics in relation to their anesthetic action (Sweet and Schroeder, 1986;Yun et al, 2002). However, while all the four local anesthetics affect the ligand binding and G-protein coupling of the serotonin 1A receptor, only tetracaine and dibucaine are found to alter the fluidity of the membrane, indicating that one cannot exclude a role for the membrane environment in the action of local anesthetics.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, one of us has previously shown that stress such as heat shock can induce anisotropic changes in membrane fluidity, i.e., the change in membrane fluidity was different when monitored in different regions in adult rat liver cells (Revathi et al, 1994). Interestingly, such depth-dependent modulation of membrane fluidity induced by alcohols (Kitagawa and Hirata, 1992) and local anesthetics (Yun et al, 2002) has also been reported. It is for this reason that we employed three fluorescent probes NBD-PE, TMA-DPH, and DPH to assess the fluidity changes induced by local anesthetics in this study.…”
Section: Effect Of Local Anesthetics On Region-specific Membrane Fluimentioning
confidence: 86%
“…Sugere-se que estes compostos se ligam a um sítio específico do canal iônico, induzindo uma mudança de conformação no receptor nicotínico, fechando-o ou impedindo a sua ativação (consequentemente inibindo o fluxo de íons pelo canal) (Yun et al, 2002;Weizenmann et al, 2012).…”
Section: Efeitos Do Par Iônico Sobre a Lipofilicidadeunclassified